Guaranteeing Fault Tolerance through Scheduling on a CAN Bus - Oliveira, M. P.; Fernandes, A. O.; Campos, S. V. A.; Zuquim, A. L. A. P. (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2003)
Prioritizing tasks in Hard-Real-Time Systems is a problem belonging to NP-hard class. Scheduling and resource allocation in real-time systems are difficult problems due to the timing constraints of the tasks involved. Scheduling policies in hard real-time systems need to ensure that tasks will meet their deadlines under all circumstances, even in the presence of faults. This work presents techniques to enhance the fault tolerance capability of multiprocessor hard real-time systems, in the presence of transient and permanent faults. As a special case, in the present paper we propose a new method to obtain a high level of fault-tolerance in the CAN bus by incorporating time redundancy and task schedulability tests, which may be used concurrently with processor redundancy and any other hardware redundancy.